WHAT KIND OF LEARNING MEDIA THAT LECTURERS AND STUDENTS WANT? NEED ANALYSIS ON HYBRID SCIENCE LEARNING: Received: 16th February 2023; Revised: 27th February 2023, 06th March 2023; Accepted: 14th March 2023 - Barokah Isdaryanti; Farid Ahmadi; Siti Nuzulia; Indah Fajarini Sri Wahyuningrum; Moh. Farizqo Irvan (PUPIL: International Journal of Teaching, Education and Learning, 2023)
The pandemic that has passed had an impact on the field of education, one of which is in hybrid science learning. This study aims to obtain information related to the learning media needed by students and lecturers in hybrid science learning. The research method applied is quantitative research with data collection techniques, namely through questionnaires. The population of this study was 120 students and 5 lecturers in the Department of Elementary School Teacher Education, Universitas Negeri Semarang. The data were analyzed using a descriptive quantitative approach. The results of the study indicate that there is a need to develop hybrid learning media in science learning. Lecturers and students agree that they need learning media that can support science learning in the form of technology-based media, contain contextual learning materials, supported by image, and can present real elements. This is assessed by lecturers and students to make it easier to understand the learning material. Thus, it can be understood that the development of science learning media with the previously mentioned criteria is needed in improving students' understanding of science concepts in hybrid science learning.